ANALYSIS OF TP53, APC, KRAS, AND MMR GENETIC MUTATIONS IN COLORECTAL CANCER: A REVIEW ARTICLE - Gavrić, Igor; Hodžić, Edin; Sarajlić, Lana; Salibašić , Mirhan; Bajramagić, Salem; Dizdarević, Advan; Kulović, Edin (Sanamed, 2024)
Introduction: Colorectal cancer (CRC) is one of the most common malignancies with significant global health and economic implications. Genetic mutations in genes such as TP53, APC, KRAS, and MMR play a crucial role in the development and progression of this cancer. This review paper analyzes current knowledge about the impact of these mutations on colorectal carcinogenesis, using available literature.Objective: To provide a comprehensive review of the role of genetic mutations in TP53, APC, KRAS, and MMR genes in the development of colorectal cancer and to consider their impact on diagnosis and treatment.Materials and Methods: This review examines peer-reviewed research articles and reports sourced from databases such as PubMed, Google Scholar, and other academic sources. The focus was on studies investigating genetic mutations, their prevalence, and their role in the pathogenesis of CRC.Results: Mutations in the TP53 gene, present in more than 50% of CRC cases, are critical for malignant cell transformations. KRAS mutations, found in about 50% of cases, lead to abnormal signaling contributing to unchecked proliferation. APC mutations are associated with hereditary predisposition to CRC, while MMR genes, such as MLH1 and MSH2, play a key role in DNA repair and are linked to hereditary nonpolyposis colorectal cancer.Conclusion: Genetic mutations in TP53, APC, KRAS, and MMR genes play a significant role in the development of colorectal cancer. A deeper understanding of these mutations may significantly enhance diagnostic and therapeutic strategies, guiding future research in this rapidly evolving field.
Keywords: Colorectal Neoplasms; Carcinogenesis; Mutation; Genes; Tumor Suppressor